Síntese e caracterização de compostos derivados do dicetopirrolopirrol para aplicações em optoeletrônica - Leithold Neto, Alfredo (2019)
The interest in the development of new materials that can be used in photovoltaic cells is increasing in the scientific scenario, due to the need to replace the energy matrixes derived from petroleum by renewable and clean energy sources of easy production. Organic photovoltaic devices have stood out in the scientific community due to the possibility of manufacturing flexible solar cells of low cost of manufacture, mainly due to the possibility of production via printing techniques. Several studies aim to improve the efficiency values of these devices, seeking the synthesis of new materials and new forms of processing. Among the materials being developed for this application, the diketopyrrolopyrrole (DPP) derivatives occupy a prominent position, being widely used as electron deficient "blocks" in the synthesis of molecules or polymers of the donor-acceptor (D - A) type. In this work DPP derivatives were synthesized and characterized, aiming the application of these compounds in organic solar cells. Preliminary studies using 2,5-dihexyl-3,6-bis(5"-hexyl- [2,2': 5',2"- thothiophene]-5-yl)pyrrolo[3,4-c]pyrrole-1,4(2H, 5H)-dione (DPP_3Th) as an active layer in a bilayer solar cell having the ITO / PEDOT: PSS / DPP_3Th: C70 / Al configuration showed an efficiency of about 1% and an open circuit potential of 0,72 V, and a short-circuit current of 2,4 mA cm-2, indicating that the results obtained are promising.